Cytogenetic and random amplified polymorphic DNA analysis of Leptodactylus species from rural and urban environments (Anura, Amphibia) - Arruda, M. P. [UNESP]; Morielle-Versute, E. [UNESP] (My University, 2008)
Cytogenetic and random amplified polymorphic DNA analyses carried out in the species Leptodactylus podicipinus, L. ocellatus, L. labyrinthicus, and L. fuscus from rural and urban habitats of the northwest region of São Paulo State, Brazil, showed that the karyotypes (2n = 22), constitutive heterochromatin distribution and nucleolus organizer region (NOR) location did not differ between the populations from the two environments. The in situ hybridization with an rDNA probe confirmed the location of the NORs on chromosome 8 revealing an in tandem duplication of that region in one of the chromosomes of L. fuscus. DAPI showed that part of the C-band-positive heterochromatin is rich in AT, including that in the proximity the NORs in L. podicipinus and L. ocellatus. The molecular analyses showed that the two populations (urban and rural) of L. podicipinus and L. fuscus are similar from a genetic point of view. The urban and rural populations of species L. ocellatus and L. labyrinthicus showed differences in genetic structures, probably due to urbanization which interferes with the dispersion of those frogs. The marked differences observed between the two populations of L. ocellatus can be representing the cryptic condition of the species. Unweighted pair-group method of analysis and genetic distance analysis detected the genetic proximity between L. ocellatus and L. fuscus. The results indicate that there was no reduction in the genetic diversity in the populations from the urban environment; however, the survival of these frogs would not be guaranteed in the case of an increase in human impact especially for populations of L. labyrinthicus and L. ocellatus. ©FUNPEC-RP.
Keywords: Amphibia; Anthropogenic; Cytogenetic; Genetic diversity; Leptodactylidae; Random amplified polymorphic DNA; ribosome DNA; animal cell; Brazil; chromosome 8; chromosome NOR; cytogenetics; DNA determination; DNA probe; frog; gene duplication; gene location; genetic variability; heterochromatin; in situ hybridization; karyotype; Leptodactylus; Leptodactylus fuscus; Leptodactylus labyrinthicus; Leptodactylus ocellatus; Leptodactylus podicipinus; nonhuman; random amplified polymorphic DNA; rural area; species habitat; survival; urban area; urbanization; animal; environment; frogs and toads; genetic polymorphism; genetics; human; karyotyping; population genetics; rural population; urban population; Anura; Animals; Cytogenetics; Environment; Genetics, Population; Heterochromatin; Humans; Karyotyping; Nucleolus Organizer Region; Polymorphism, Genetic; Rural Population; Urban Population